Neo-Pentecostalism and religious conservatism on Facebook: A digital ethnography in Peruvian Pro-Family and Pro-Life groups - Muro Ampuero, Eduardo (2022)
This article is situated in the galloping rise of a conservatism that seeks to mold society according to moral standards based on a rigid religiosity that advocates the defense of the «traditional family», the fight against homosexualization of children, and communism. The main actors have been collectives that call themselves Pro-family and Pro-life and have a close relationship with ultra-conservative religious groups; being the Evangelical-Neopentecostals who have led these movements. Thus, it is assumed that these groups have a religious substratum based on the political theology of neo-Pentecostalism. Considering the lack of digital ethnographic research on this phenomenon, this paper seeks to delve into the ideal of society that the Facebook followers of these collectives want for Peru and the (dis)connections that may exist between them and Peruvian Neo-Pentecostalism.